Proyecto a nivel de ejecución de la carretera Saposoa – Paltaico - Paredes Vasquez, Rene Baudilio (2003)
The present work of thesis to obtain the professional title of Civil Engineer, has been developed in order to make a scientific contribution to help solve a problem of local roads, that will provide a road section which contributes to the socioeconomic development of the beneficiaries to be executed. Research is applied and it has been conducted at the Faculty of Civil Engineering, Universidad Nacional de San Martín, developing the project in the province of Mariscal Cáceres, this work has been developed by applying the field theories and standards existing topography, mechanics of soils, hydrology, environmental impact and road drainage, concrete and other related , and which have allowed to have the final draft of the road section already named. The results obtained demonstrate clearly that it is possible to achieve the correct application of the theories, studies and results...